2017
DOI: 10.1158/1055-9965.epi-16-0343
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Breast Cancer Prognosis: A Systematic Review

Abstract: Telomeres ensure genome integrity during replication. Loss of telomeric function leads to cell immortalization and accumulation of genetic alterations. The association of telomere length (TL) with breast cancer prognosis is examined through a systematic review. Electronic databases (MEDLINE, EMBASE, CENTRAL), from inception to December 2015, and relevant reviews were searched. Studies that evaluated TL (blood and/or tumor) in association with breast cancer survival or prognostic factor were included. Thirty-si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 58 publications
2
42
1
Order By: Relevance
“…The same observation was made for other modifiable factors (BMI, smoking, alcohol consumption) which were found to be associated with shorter telomere length in healthy women [7, 10], but not in breast cancer patients [15]. Only two studies have assessed the associations of tumor prognostic factors with peripheral blood cell relative telomere length, and one reported no association with ER status after adjustment for age [15, 29]. Moreover, longitudinal cohort studies suggest that telomere length might be an independent prognostic factor [15].…”
Section: Discussionmentioning
confidence: 57%
“…The same observation was made for other modifiable factors (BMI, smoking, alcohol consumption) which were found to be associated with shorter telomere length in healthy women [7, 10], but not in breast cancer patients [15]. Only two studies have assessed the associations of tumor prognostic factors with peripheral blood cell relative telomere length, and one reported no association with ER status after adjustment for age [15, 29]. Moreover, longitudinal cohort studies suggest that telomere length might be an independent prognostic factor [15].…”
Section: Discussionmentioning
confidence: 57%
“…Perceived stress and cortisol reactivity to stress are associated with shorter telomere length (Parks et al, 2009; of chromosomes that become shorter with each cell division until reaching a limit at which point cell apoptosis or loss of cell function occurs. Shorter telomere length is associated with cardiovascular disease (Fitzpatrick et al, 2006), cancer (Ennour-Idrissi, Maunsell, & Diorio, 2017), and mortality (Cawthon, Smith, O'Brien, Sivatchenko, & Kerber, 2003). A meta-analysis of seven trials studying the impact of nutrition on telomere length reported no significant relationship; however, all trials have been conducted in adult populations and the meta-analysis noted strong heterogeneity among the studies in terms of type and duration of dietary intervention (P erez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that MSCs promised to be an effective therapy for brain injury in TBI [175-177, 215, 231-236]. Instead of brain remodeling and functional recovery by cell replacement effects, evidence suggests that the major effects of neurorestoration were due to the paracrine effects of secretion-based factors such as MSCs-derived exosomes that may reduce neuroinflammation, promote neurogenesis and angiogenesis, rescue pattern separation and spatial learning impairments, and improve functional recovery after TBI in animal models [107,176,178,191,204,205,215,216,[235][236][237]. In addition, as exosomes contain various miRNAs, which play a key role in modifying the phenotype and/or the physiology and modulating the cellular processes of the recipient cell, and miRNAs such as miR-21 could be potential therapeutic targets for interventions after TBI, the combination of miRNAs and MSC-derived exosomes might be a novel approach for the treatment of TBI [238].…”
Section: Extracellular Vesicles and Exosomesmentioning
confidence: 99%